The Influence of Relational Context on the Decision to Pursue a Master’s Degree - Hall, Véronique; LeBreton, Diane (Canadian Journal of Counselling and Psychotherapy, 2013)
This article presents research results on the influence of the relational context in the decision to pursue a master’s degree. Thematic analysis of data collected from interviews made it possible to identify the individuals who influence the decision and how they exert that influence. Among the main themes that emerge are providing support, facilitating exploration, and acting as a role model. The research results underline how important it is for career counsellors to recognize the role others play in the decision-making process.